Permainan Edukatif Dalam Meningkatkan Prestasi Belajar Anak Usia Dini Pada Sentra Iman dan Taqwa (IMTAQ) di TK Islam Ar-Rosyiid - Vellia Novianty Malik (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2021)
This research is motivated by the lack of learning achievement of early childhood in religious values. This is due to the lack of providing material regarding religious insights and the ineffective methods used during learning which results in early childhood understanding of religious values ​​and good behavior habits. Therefore this research will discuss further about the media used, namely educational games in the learning process at the center of faith and piety (imtaq) in order to create a pleasant learning atmosphere with the aim of increasing early childhood learning achievement, especially in religious insight and values. morals that will be applied in everyday life. This research uses qualitative research with descriptive methods. From the results of this study it can be concluded that (1) the learning process at the center of faith and piety (imtaq) is the right method in increasing the insight into early childhood equality, (2) the role of educational games is very effective in improving learning achievement of early childhood, (3) the obstacles faced to improve early childhood learning achievement through educational games.